2017
DOI: 10.21037/tp.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

The female athlete triad: special considerations for adolescent female athletes

Abstract: The number of adolescent girls participating in sports has dramatically increased throughout the last few decades. In the early 1990's, an association between amenorrhea, osteoporosis, and disordered eating was recognized and eventually labeled the 'Female Athlete Triad'. In 1997, the Task Force on Women's Issues of American College of Sports Medicine (ACSM) published a position statement on this triad of conditions that were becoming increasingly more prevalent amongst female athletes. Initially, the 'Female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
17
0
4
Order By: Relevance
“…Energy deficit and low leptin levels resulting from caloric insufficiency lead to decreases in luteinizing hormone pulse frequency and the hypothalamic release of gonadotropin-releasing hormone, resulting in a hypoestrogenic state. 20 We found that 29.3% of the 78 participants not using oral contraceptives lacked monthly menstrual cycles. This is consistent with the 31% prevalence of menstrual irregularity in a sample of 425 female collegiate athletes 21 and considerably higher than the 14% prevalence in female college students in general.…”
Section: Female Athlete Triad Componentsmentioning
confidence: 69%
See 1 more Smart Citation
“…Energy deficit and low leptin levels resulting from caloric insufficiency lead to decreases in luteinizing hormone pulse frequency and the hypothalamic release of gonadotropin-releasing hormone, resulting in a hypoestrogenic state. 20 We found that 29.3% of the 78 participants not using oral contraceptives lacked monthly menstrual cycles. This is consistent with the 31% prevalence of menstrual irregularity in a sample of 425 female collegiate athletes 21 and considerably higher than the 14% prevalence in female college students in general.…”
Section: Female Athlete Triad Componentsmentioning
confidence: 69%
“…A negative energy balance, such that nutritional intake is insufficient to meet both the demands resulting from physical training and normal physiological functions, drives the pathophysiology of the female athlete triad. 20 Although an eating disorder is not always diagnosed clinically, disordered eating behaviors are often present. Female athletes face numerous pressures to be thin, ranging from performance-related to social factors.…”
Section: Female Athlete Triad Componentsmentioning
confidence: 99%
“…Certainly, the decision requires coaches' knowledge of medical and psychological indicators of eating disorders, as highlighted by Sherman & Thompson (2001), even though the athlete must be recovered, both psychologically and medically, before she can return to train (De . Started by saying that the management of female athlete RED-S should have a multiple disciplinary approach, the first intervention must focus on the low energy state (Brown, Dewoolkar, Baker & Dodich, 2017). Once again, treatment strategy involves an increase in energy intake, reduction in exercise or a comthienbination of both (Guebels, Kam, Maddalozzo & Manore, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach is crucial for a successful treatment (Warr & Woolf, 2011). The coaches have to provide a continuative education regarding the correct eating and training behaviors and contribute to the good health and high performance of their athlete with preventive strategies (Brown et al, 2017)…”
mentioning
confidence: 99%
“…However, engaging in sport can also be a risk factor for unhealthy behaviours, high training loads and metabolic disturbances in a subset if vulnerable athletes [4]. An official document entitled Female Athletes Issues for the Team Physician: A Consensus Statement -2017 Update confirms that female athletes suffer musculoskeletal injuries and medical problems that come from and/or impact athletic activity.…”
mentioning
confidence: 99%